四圆弧齿廓齿轮啮合特性的进一步探讨 - 许义泉; 康星虎 (Jixie chuandong)
By applying graphic method to analysis the meshing characteristic of quadruple-arc gear.The following results are obtained:① the calculation of axial distance of four simultaneous meshing points of quadruple-arc gear,② the calculation formula of multi-point mesh factor and multi-pairs tooth mesh factor of quadruple-arc gear,③ the relationship of tooth width related to multi-pairs tooth mesh factor and multi-point mesh factor.